Tindak Tutur Ilokusi dalam Ujaran Kebencian pada Kolom Komentar Video 4K ‘Easy’ (Le SserafimFancam No. 1 Encore) pada Kanal Youtube M2 - Farrah Anggia Tsuraya (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to analyze the illocutionary speech acts in hate speech in the comment section of the 4K video 'easy' (Le Sserafim Fancam, No. 1 Encore) on the youtube channel M2. In analyzing the research focus, the author uses a pragmatic approach with a qualitative-descriptive research method. qualitative-descriptive research method. The data collection stages are carried out with and documentation techniques. This research describes: (1) how the form of hate speech contained in the comment section of the 4k 'easy' video (Le Sserafim Fancam No. 1 Encore) on the M2 YouTube channel, (2) how are the types of hate speech contained in the comment section of the 4k 'easy' video Encore) on YouTube channel M2, (2) how the types of illocutionary speech acts contained in the comments on the video on the YouTube channel. The result shows that there are 4 types of illocutionary speech acts, among others, assertive illocutionary speech acts (5), directive illocutionary speech acts (3), commissive illocutionary speech acts (2), and expressive illocutionary speech acts (5). And there are 3 forms of hate speech There are also 3 forms of hate speech contained in illocutionary speech acts.